The breaking point - Hemingway, Ernest 1899-1961; Steiner, Max 1888-1971 (<<The>> Criterion Collection, 2017)
"Michael Curtiz brings a master skipper’s hand to the helm of this thriller, Hollywood’s second crack at Ernest Hemingway’s To Have and Have Not. John Garfield stars as Harry Morgan, an honest charter-boat captain who, facing hard times, takes on dangerous cargo to save his boat, support his family, and preserve his dignity. Left in the lurch by a freeloading passenger, Harry starts to entertain the criminal propositions of a sleazy lawyer (Wallace Ford), as well as the playful come-ons of a cheeky blonde (Patricia Neal), making a series of compromises that stretch his morality—and his marriage—further than he’ll admit. Hewing closer to Hemingway’s novel than Howard Hawks’s Bogart-Bacall vehicle does, The Breaking Point charts a course through daylight noir and working-class tragedy, guided by Curtiz’s effortless visual fluency and a stoic, career-capping performance from Garfield." [filmdienst.de]
Original: USA 1950
Blu-ray special edition features: new 2K digital restoration, with uncompressed monaural soundtrack ; new interview with critic Alan K. Rode (Michael Curtiz: A Life in Film) ; new piece featuring actor and acting instructor Julie Garfield on her father, actor John Garfield ; new video essay by Taylor Ramos and Tony Zhou analyzing Curtiz’s methods ; excerpts from a 1962 episode of "Today" showing contents of the Ernest Hemingway house in Key West, Florida, including items related to "To have and have not", the novel on which "The breaking point" is based ; trailer ; English subtitles for the deaf and hard of hearing ; plus: An essay by critic Stephanie Zacharek
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc